Lembaga tahfizh Al-Qur’an dalam sejarah pendidikan Islam - Muhammad Jakfar; Abdul Rauf Haris; Fahmi Zulfikar (LPPM Universitas Ibn Khaldun, Bogor, 2020)
This paper studies a number of questions about the Quran recitation, including the background that encouraged the birth of the Quran recitation activities in the history of Islamic education, since when it emerged and how the history of the development of educational institutions. The research was conducted by library research method by reading a number of historical books on the development of Islamic education during the time of Rasulullahah PBUH until the current development. From the results of the study it was concluded that first, the emergence of the activities of the Tahfizh al Quran was motivated by oral traditions which were more dominant in the Arabs during the time of the Prophet's preaching. Thus, the revelations that came down and were taught by the Prophet were memorized more. Secondly, the memorizing of al Quran appears with the start of the Islamic preaching by the Messenger of Allah. Under the direct guidance of the Messenger, the Companions who were dominated by ahlush shuffah memorized the Quran and make their readings. In further developments, as a special educational material, the tahfizh al Quran grew even more when the function of the mosque as a community education institution was greater and with the emergence of kuttab during the Umayyad era. Third, the tahfizh al Quran has become a scientific tradition that continues to exist even though its institutional form has evolved from the form of mosque schools, kuttab, palace schools, madrasas to universities. AbstrakArtikel ini meneliti beberapa pertanyaan tentang tahfizh al Quran mencakup latar belakang yang mendorong lahirnya kegiatan tahfizh al Quran dalam sejarah pendidikan Islam, sejak kapan muncul dan bagaimana sejarah perkembangan lembaga pendidikannya. Penelitian dilakukan dengan metode riset kepustakaan dengan membaca beberapa buku sejarah perkembangan pendidikan Islam pada masa Rasulullaah saw hingga perkembangan saat ini. Dari hasil kajian disimpulkan bahwa pertama, munculnya kegiatan tahfizh al Quran dilatarbelakangi tradisi lisan yang lebih dominan pada bangsa Arab pada masa dakwah Rasulullah. Sehingga, wahyu yang turun dan diajarkan oleh Rasulullah lebih banyak dihafal. Kedua, tahfizh al Quran muncul seiring dimulainya dakwah Islam oleh Rasulullah. Di bawah bimbingan langsung Rasulullah, para shahabat yang didominasi ahlush shuffah menghafal al Quran dan memperdengarkan bacaannya. Dalam perkembangan selanjutnya, sebagai materi pendidikan khusus, tahfizh al Quran semakin berkembang ketika fungsi masjid sebagai lembaga pendidikan masyarakat semakin besar dan seiring munculnya kuttab pada masa Umayyah. Ketiga, tahfidz al Quran menjadi tradisi keilmuan yang tetap ada meskipun bentuk kelembagaannya mengalami perkembangan dari mulai bentuk sekolah masjid, kuttab, sekolah istana, madrasah hinga perguruan tinggi.